Microscopic, Multipoint Characterization of Foreshock Bubbles With Magnetospheric Multiscale (MMS). Issue 7 (25th June 2020) - Turner, D. L.; Liu, T. Z.; Wilson, L. B.; Cohen, I. J.; Gershman, D. G.; Fennell, J. F.; Blake, J. B.; Mauk, B. H.; Omidi, N.; Burch, J. L.
Abstract: This work presents the first detailed analysis of foreshock bubbles (FBs) using high‐resolution Magnetospheric Multiscale (MMS) data. Between October 2017 and January 2019, MMS captured 10 foreshock transient events with burst resolution data that we show are consistent with FBs. One "textbook" event is examined and described in detail. Employing the multipoint nature of MMS, we demonstrate how the size and orientation, expansion speed, and distance since formation can be estimated. From all 10 events, FB sizes ranged from 1.1 to 9.9 RE (average of 4.4 RE ), and expansion speeds ranged from 139 to 377 km/s (average of 257 km/s). FBs formed under a usual range of solar wind conditions between 3 and 20 RE upstream of Earth's bow shock. We also report on new features of FBs: deep and localized magnetic "holes" within the cores of FBs, where the total field strength drops to <1 nT. Key Points: Foreshock bubbles (FBs) are large (up to 10 RE ), explosive (expansion speeds of >100 km/s) events upstream of the bow shock FBs form under a usual range of solar wind conditions between 3 and 20 RE upstream of Earth's bow shock FB cores often include deep, localized magnetic holes where the B field drops to <1 nT